EFFECTIVE METHODS FOR TEACHING ENGLISH TO ELEMENTARY SCHOOL STUDENTS (International journal of artificial intelligence, 2025)
This article analyzes effective methods of teaching English to primary school students. The study was conducted on the basis of existing scientific literature, studying modern pedagogical approaches, teaching methods and their effectiveness.